PENGARUH METODE PEMBELAJARAN INKUIRI TERBIMBINGTERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA : Studi Kuasi Eksperimen Pada Materi Strategi Promosi Makanan Khas Asli Daerah Prakarya Dan Kewirausahaan Kelas XI SMA Negeri 21 Jakarta - Widiasari, - (2023)
This research is motivated by a paradigm shift in the learning process in accordance with the technological era or industrial revolution 4.0, the ability that needs to be taught to students in this century, one of which is the ability to think creatively. The purpose of this research is to find out 1). Differences in students' creative thinking abilities in the experimental class before and after using the guided inquiry learning method. 2). Differences in students' creative thinking abilities in the control class before and after using the problem solving learning method, 3). Differences in improving students' creative thinking abilities between the experimental class using the guided inquiry method and the control class using the problem solving method in entrepreneurship subjects. The research method used is a quasi-experimental method with the Nonequivalent Control Group Design. The research subjects consisted of two classes, namely class XI 4 (experimental class) and XI 1 (control class). Pretest and posttest tests were used to collect data. Data processing was carried out using the t-test (pairedsample t-test) and independent sample t-test using the SPSS application program. 24. Based on the research results show that 1). There are differences in the level of students' creative thinking abilities in the experimental class before and after using the guided inquiry learning method in the medium category; 2). There are differences in the level of students' creative thinking abilities in the control class before and after using the problem solving learning method with a low category; 3). There are differences in students' creative thinking abilities in the experimental class and the control class, the increase in students' creative thinking skills using the guided inquiry method is higher than the increase in students' creative thinking abilities using the problem solving method.